Exploit Physiological Efficiency to Overcome Planting Time Barrier in Wheat and Develop Varieties Suitable for per day Productivity: Enhancing Wheat Productivity via Physiological Efficiency - Devinder Mohan; Sareen, Sindhu; Jha, Ankita (Journal of Cereal Research, 2025)
Varieties evaluated by All India Coordinated Research Programme on Wheat and Barley (AICRPWB)during the period 2000-23 were assessed in four zones of Indian plains. The purpose was to test whether the timely and late sown genotypes were really exclusive for these two production conditions. Physiological efficiency was used as the primary distinguishing tool in Advance Varietal Yield Trials of timely sown and late sown conditions. Application of six physiological parameters made it amply clear that most of the varieties were physiologically efficient in overcoming the hurdles of planting time in three zones namely North Easter Plains Zone (NEPZ), Central Zone (CZ) and Peninsular Zone (PZ). Situation was quite different in the most productive wheat land of the country i.e. North Western Plains Zone (NWPZ). Although majority of the timely sown varieties did qualify for late-sown condition in this zone but only few late-sown varieties could meet the efficiency level of timely sown condition. This analysis suggests that the pre-released varieties of both sowing conditions should be tested together under both sowing dates against the popular checks of both sowing conditions. Assessment on the basis of per day productivity has also suggested as an alternate pathway. The predictors have been suggested for each zone to formulate an ideotype-based breeding strategy.